Hubungan Penggunaan Gadget dengan Tingkat Kecerdasan Generasi Alpha di MTs Miftahussalam Demak - Aliyatul Khusna; Nopi Nur Khasanah; Kurnia Wijayanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Advances in digital technology have brought about major changes in the behavior patterns and ways of thinking of the younger generation, including Generation Alpha, who live in a fully digital environment. Uncontrolled use of gadgets can affect children's cognitive, emotional, social, and spiritual aspects. This study analyzes the relationship between gadget use and intelligence levels among Generation Alpha at MTs Miftahussalam Demak. This study uses a quantitative correlation design with a cross-sectional approach. The population consists of 200 students, and the sample consists of 66 Generation Alpha students selected using purposive sampling. The measuring instrument used is a closed questionnaire that has been tested for validity and reliability. Data analysis was performed using univariate and bivariate analysis with Spearman's rank correlation test at a significance level of 0.05. The results showed that most respondents used gadgets for a short time (<2 hours per day) (47%), while the majority had good (54.5%), fair (37.9%), and poor (7.6%) intelligence levels. Bivariate analysis showed a strong and significant relationship between gadget use and intelligence level (r = -0.662; p = 0.000 < 0.05). A negative correlation means that the higher the intensity of gadget use, the lower the students' intelligence level.